"A sorely neglected field": A multisite study of self‐reported humanities exposure among emergency medicine residents. Issue 3 (29th June 2022) - Balhara, Kamna S.; Irvin, Nathan; Zink, Korie L.; Mohan, Sanjay; Olson, Adriana S.; Tackett, Sean; ,; Regan, Linda
Abstract: Background: The Association of American Medical Colleges has identified the humanities as fundamental to medical education across all specialties. Evidence from undergraduate medical education (UME) demonstrates the humanities' positive impacts on outcomes that could be relevant to patient care and trainee well‐being in emergency medicine (EM) residency training. However, less is known about the humanities' role in graduate medical education (GME). Objectives: The objectives were to describe EM residents' self‐reported exposure to the humanities and its relationship with their empathy, tolerance of ambiguity, and patient‐centeredness, and to assess their attitudes toward the humanities in GME. Methods: This cross‐sectional survey‐based study was conducted at six U.S. EM residency programs in 2018–2019. Quantitative analyses included linear regressions testing for trends between humanities exposures and outcomes, adjusted for sex, year in training, and clustering within programs; adjunct analysis of free‐text responses was performed using an exploratory constructivist approach to identify themes about views on the humanities' role in medicine. Results: Response rate was 54.8% (153/279). A total of 65% of respondents were male and 28.1% of respondents had a preceding humanities degree. Preceding humanities degree and current self‐reported humanities exposure were positively associated with performance on empathy subscales ( p = 0.02). Seventy‐five percent ( n = 114) of respondents agreed humanities are important in GME; free‐text responses revealed perceived positive impacts of humanities on generating well‐rounded clinicians and enhancing patient care. Conclusions: Engagement with the humanities may be associated with empathy among EM residents. Although the magnitude of associations was smaller than that seen in UME, this study demonstrates resident interest in humanities and suggests that extracurricular engagement with the humanities may be insufficient to prolong positive impacts seen in UME. Further research is needed to explore how to sustain these benefits through integration or addition of the humanities in existing GME curricula.